First record of Calma gobioophaga Calado and Urgorri, 2002 (Gastropoda: Nudibranchia) in the Mediterranean Sea - PRKIC, J.; FURFARO, G.; MARIOTTINI, P.; CARMONA, L.; CERVERA, J. L.; MODICA, M. V.; OLIVERIO, M. (Mediterranean Marine Science, 2014)
Specimens of the nudibranch genus Calma were observed under stones at two Croatian localities while feeding on gobiid eggs. Some ambiguous morphological features compared with the original descriptions of the known species of the genus, C. glaucoides and C. gobioophaga, hampered an easy identification. Genetic data (COI and 16S sequences) confirmed the distinction between the two species of the genus Calma, and allowed to unambiguously identify the Croatian specimens as Calma gobioophaga. This is the first record of this species for the Mediterranean and extends remarkably its distribution range. Finally, the eggs fed by the Croatian specimens have been taxonomically identified by using the 12S rDNA marker as Gobius cobitis.